Bhutan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper and Statistical Appendix on Bhutan underlie the macroeconomic impact of Tala, rapid private sector credit growth, and macroeconomic risks. In Bhutan, as the bulk of Tala-related flows go through the government accounts, this requires an appropriate fiscal stance and skillful expenditure management. Strong economic growth will require and lead to a deepening and further development of the financial system in Bhutan. The financial sector seems to be relatively shielded from adverse events, although risks remain.